Cabin in the snow can Charlie prove he can be responsible? - Hopkinson, Deborah; Faricy, Patrick (New York Aladdin Paperbacks, 2002)
While Papa is off fighting on the Missouri border, Charlie is left in charge of the family in their remote cabin in Bleeding Kansas and so must keep everyone safe when a fierce prairie blizzard growls and rages outside their door.
580L
84384
Keywords: Blizzards -- Fiction; Frontier and pioneer life -- Kansas -- Fiction; Family life -- Kansas -- Fiction; Kansas -- Fiction